(untitled) (Research, Society and Development, 2022)
Ethnomycology studies the relationship between man and fungus, seeking to address how environmental and socioeconomic aspects can affect the knowledge and use of fungal resources in a given community. In this perspective, this study aimed to carry out a survey on popular knowledge about macrofungi present in urban backyards at Benjamin Constant (AM). Thus, 20 properties were randomly selected in the Castanhal neighborhood, where semi-structured interviews were carried out, with the support of a photographic album previously made with local species. The information resulting from the interviews was filtered, tabulated and evaluated through descriptive and exploratory statistics into Excel® v. 2019 and SigmaPlot® v. 11. We observed the presence of 360 macrofungi distributed in 19 families, of which approximately 95% belonging to the phylum Basidiomycota and only 5% to the phylum Ascomycota. Twenty people were interviewed, with a predominance of female audience (80%) and age group ranging from 25 to 60 years. The perception of the residents regarding the macrofungi present in their backyards was diverse, however, the majority (45%) classified them as plant diseases. In general, knowledge about the applicability and ecological importance of fungi is fundamental for maintenance of biodiversity. However, the results show that the residents of the Castanhal neighborhood are unaware of the importance of macrofungi and associate them with disgusting and harmful things. Thus, it is essential that actions aimed at disseminate and popularizing the role of these organisms in the environment are carried out, thus contributing to the conservation of fungal biodiversity.